Developing Self-Efficacy in Public Speaking Using Video and Digital Oratory on YouTube. Issue 2 (June 2023) - Sharma, Daneshwar
Digital communication and digital oratory have become an integral part of today's workplace. This research discusses an innovative assessment tool that uses digital oratory and digital video along with YouTube to create opportunities for the students to develop self-efficacy in digital oratory and public speaking. The measurement of the effectiveness through a survey questionnaire displays that the assessment tool met its learning objectives. The assessment tool fostered self-efficacy in digital oratory and improved digital communication knowledge and skills. The article also discusses the challenges and recommendations for implementing this assessment tool in various contexts.